Atractylone Alleviates Ethanol-Induced Gastric Ulcer in Rat with Altered Gut Microbiota and Metabolites - Li L; Du Y; Wang Y; He N; Wang B; Zhang T (Dove Medical Press, 2022)
Ling Li,1,2,* Yaoyao Du,1,* Yang Wang,3 Ning He,2 Bing Wang,1,4 Tong Zhang1 1School of Pharmacy, Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of China; 2School of Pharmacy, Anhui University of Chinese Medicine, Hefei, People's Republic of China; 3Metabo-Profile Biotechnology (Shanghai) Co. Ltd, Shanghai, People's Republic of China; 4Chinese Academy of Sciences, Shanghai Institute of Materia Medica, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Bing Wang; Tong Zhang, Email bwang@simm.ac.cn; zhangtdmj@hotmail.comBackground: Gastric ulcer (GU) is the most common multifactor gastrointestinal disorder affecting millions of people worldwide. There is evidence that gut microbiota is closely related to the development of GU. Atractylone (ATR) has been reported to possess potential biological activities, but research on ATR alleviating GU injury is unprecedented.Methods: Helicobacter pylori (H. pylori)-induced GU model in zebrafish and ethanol-induced acute GU model in rat were established to evaluate the anti-inflammatory and ulcer inhibitory effects of ATR. Then, 16S rRNA sequencing and metabolomics analysis were performed to investigate the effect of ATR on the microbiota and metabolites in rat feces and their correlation.Results: Therapeutically, ATR inhibited H. pylori-induced gastric mucosal injury in zebrafish. In the ulceration model of rat, ATR mitigated the gastric lesions damage caused by ethanol, decreased the ulcer area, and reduced the production of inflammatory factors. Additionally, ATR alleviated the gastric oxidative stress injury by increasing the activity of superoxide dismutase (SOD) and decreasing the level of malondialdehyde (MDA). Furthermore, ATR played a positive role in relieving ulcer through reshaping gut microbiota composition including Parabacteroides and Bacteroides and regulating the levels of metabolites including amino acids, short-chain fatty acids (SCFAs), and bile acids.Conclusion: Our work sheded light on the mechanism of ATR treating GU from the perspective of the gut microbiota and explored the correlation between gut microbiota, metabolites, and host phenotype.Keywords: atractylone, gastric ulcer, inflammation, oxidative stress, gut microbiota, metabolomics